Selective Small Molecule Myeloid Cell Leukemia-1 (MCL-1) Inhibitors: Novel Agents in Cancer Therapy - Hoda Sobhy Ibrahim; Deena S. Lasheen; Rabah A. T. Serya; Dalal Abd-ELRahm (Ain Shams University, 2019)
Apoptosis is a normal physiological process which is very crucial to maintain tissue homeostasis. Dysregulated apoptosis can lead to various diseases as cancer. Thus, evasion of apoptosis stands out as a key hallmark of cancer cells. Bcl-2 family of proteins is the key modulator of the mitochondrial apoptotic pathway. Therefore, the balance between the anti-apoptotic (BCL-2, BCL-XL and MCL-1) and pro-apoptotic (BAK, BAX, BAD, PUMA and NOXA) members of this family will govern cell fate. Overexpression of anti-apoptotic BCL-2 members including MCL-1 is implicated in the progression of many human cancers as well as the emerging resistance to various anti-cancer agents including targeted therapies. Indeed, inhibition of the anti-apoptotic BCL-2 members by small molecule BH3 mimetics may provide an excellent approach in cancer therapy. Unfortunately, it was reported that MCL-1 overexpression is linked to Venetoclax, first FDA approved BCL-2 selective inhibitor, resistance in AML. Thus, inhibition of MCL-1 with a selective small molecule inhibitor may provide an attractive strategy in cancer targeted therapy. Recently, several small molecule MCL-1 selective inhibitors have been developed and few are testing in clinical trials. Herein, we will discuss the recent advances in the development of selective small molecule MCL-1 inhibitors.